Pregnancy outcome after cervical conisation: A 2nd retrospective cohort study in the Leuven University Hospital. (September 2017) - van Velthoven, Kim; Poppe, Willy; Verschuere, Hannah; Arbyn, Marc
Abstract: Objective: To evaluate whether the dimensions of the cones removed during large loop excision of the transformation zone have decreased over time. Secondly, whether these changes were associated with a lower risk of obstetrical harms on a subsequent pregnancy. Study design: A retrospective matched cohort study was performed in a tertiary referral unit in Belgium. A total of 97 women were identified from a database of women who underwent excisional treatment for cervical precancer between January 1st, 2004 and December 31st, 2012, and delivered before December 31st, 2014. The control group consisted of 120 non-treated women who had no history of cervical intra-epithelial neoplasia. Data on smoking status; gestational age at delivery; number of conisations; time interval between treatment and pregnancy; dimensions of the cone; severity of the lesion; and the extra resection of endocervical tissue were collected. These data were compared with those from a previous similar study at the University Hospital of Leuven in 2009, which database we enriched with information on the cone dimensions. Main outcome variables were gestational age at delivery, birthweight and neonatal condition at birth. Results: Only a significant lower birthweight could be found in the treated group compared to the control group (3364 g [95% CI 3094–3290] versus 3364 g [95% CI 3253–3475], P = 0.023). The current study showed no increase in preterm birth rate after conisation and no relationship between volume or depth of the cone and preterm birth could be found. Over the period 1999–2014, a significant decrease in all dimensions was observed: on average −0.3 mm, −0.3 mm, −0.4 mm and −132 mm 3 per year, for the depth, anteroposterior and transverse diameter and the volume, respectively. Conclusions: Our two successive studies showed a significant trend towards smaller cones which was accompanied by a decrease in preterm birth after excisional treatment. The clinician could limit the size of the cone to avoid obstetrical harms, but needs to be aware of the oncological safety as well.